DAB+ Network Implementation in the Czech Republic and Impact of the Audio Coding on Subjective Perception of Sound Quality - K. Zyka (Radioengineering, 2020)
Digital Audio Broadcasting (DAB+) is becoming a reality in the Czech Republic. The first nationwide DAB+ network, based on the regular broadcasting, is being completed. This paper presents the principles that were used to achieve a quick and efficient penetration of the DAB+ signal in the Czech population and the highways. Attention is focused on practical experience with the use of High-Efficiency Advanced Audio Coding (HE-AAC) emphasizing maximum efficiency of the multiplex. This is done with respect to the subjective perception of sound quality by the audience. Final audio processing and appropriate signal pre-processing are considered. The paper also focuses on how to use Forward Error Correction (FEC) coding to increase the reach of transmitters and the reasons for employing the specific transmitter network configuration, including indoor reception. The results of this complex method are demonstrated on the network rollout in particular periods, while the key assumptions were verified. The entire development process can be monitored on the maps of coverage.